Immigration and trust in politics in Britain - McLaren, Lauren M. (Cambridge University Press, 2011)
This paper argues that a previously overlooked explanation for varying individual-levels of political trust is concern about immigration. Focusing on the case of Britain, where levels of opposition to immigration have remained high since the 1960s and yet the implications of such opposition are still unclear, this paper examines the effect of concern about immigration on political trust. Using the pre- and post-election panel component of the 2005 British Election Study and the 2002-3 European Social Survey, we illustrate that after controlling for a wide range of other predictors of trust in politics, concerns about the impact of immigration significantly affect political trust. In addition, in 2005 the perception that government had not handled the issue of immigration effectively also significantly affected political trust, with both linear and interactive effects.